Analysis Of The Marketing Mix And Its Influence On Purchasing Decisions On The Prasetya Products - Tien Yus Tini; Yuliza Betty Harleoni; Marzuki Alie (UNIVED Press, 2024)
This study aims to identify, study and analyze the marketing mix of The Prasetya and The Influences in Customer Decisions to by product of The Prasetya. This study used qualitative research methods, with data collection techniques observation, interviews and explore theh types of open-ended questions where information is free to provide in depth information to be used as research data. The data analyzed is the result of interviews with employees, customers and experienced human resourch of UMKM using analyctical techniques including data reduction, data presentation and levers or cunclusions. The result of this study that marketing mix of The Prasetya has been able to influence consumer purchasing decisions and increase sales turnover and customers always make repeat purchases for the product and also increase the company's profits so that the company's goals can be achieved.